Pemberdayaan Kelompok Posyandu melalui Program Mandiri Lawan DM Berbasis Kearifan Lokal di Desa Poto - Abdul Hamid; Nurlaila Agustikawati; Lina Eta Safitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
Complications of Diabetes Mellitus often arise and without being realized have developed to cause acute and chronic complications that make it difficult for DM sufferers to maintain their condition and will affect the condition of DM sufferers that impact the quality of life of sufferers. Consuming too many carbohydrates causes insulin in the body to work extra, so that the insulin's ability to work in the body will be reduced, which can cause blood sugar to rise. Nutritional therapy can be done by replacing carbohydrate intake with tubers that are low in glucose levels, one of which is Ganyong and pharmacological therapy through herbal medicines, one of which is sentalo leaf tea which is easily obtained and inexpensive. The objectives of this community service activity are to improve the knowledge, skills and quality of service of partners in the implementation of family posyandu related to DM. The method used is empowering posyandu groups through educational activities and training. The results of this activity show an increase in knowledge and skills of partners before and after the community service activity was carried out. And an increase in visits to the posyandu after the implementation of PMT using ganyong flour as the raw material.